BENTUK PENYAJIAN TARI ENTARAI MASYARAKAT SUKU DAYAK KETUNGAU SESAEK DI KECAMATAN SEKADAU HILIR KABUPATEN SEKADAU - Emelia, Mela; Ismunandar, Ismunandar; Fertisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study analyzes the presentation form of Entarai Dance in the Sesaek Ketungau Dayak Tribe in Sekadau Hilir Subdistrict, Sekadau District, which is motivated by the researchers' desire to make complete documentation about Entarai Dance. The formulation of the research problem is, 1) What is the form of presentation of Entarai Dance, Dayak Ketungau Sesaek Tribe, 2) How is Entarai dance teaching material for art and culture lessons and skills at the eighth grade junior high school level. This study uses descriptive methods in the form of qualitative research and uses a choreographic approach. Data collection techniques use observation, interview and documentation techniques. Techniques to test the validity of the data using extended observations and Triangulation (Source Triangulation). Based on the analysis Entarai dance has a form of presentation in the form of initial motion, middle / core, and cover. The elements contained in the other forms of presentation are, circular floor design, top design, symmetrical design design, angular design, contrast, horizontal top design, simultaneous design group composition, non-literary theme, outdoor show place, simple makeup , women's clothing kebaya, batik skirts, scarves, men's clothing batik clothes and cloth pants, musical accompaniment of four gongs and canoes, Property shawls, sea cucumber flowers, tepayan containing tuak and small bamboo, tabas. The results of this study are expected to be contributed as teaching material to understand Entarai dance, and Entarai dance demonstration in class VIII, semester 1, in the 2013 curriculum. Keywords: Presentation Form, Entarai, Ketungau Sesaek, Sekadau Hilir District